Genotypic and Serotypic confirmations of Bacterial community to Kotumsar cave for occupational safety of cave workers and visitors from pathogenic threats - Rajput, Yogita; Neral, Arvind; Rai, Vibhuti (International Journal of Occupational Safety and Health, 2017)
Background: Bacterial communities exist everywhere in the universe so in the caves. Kotumsar cave is the one of the renowned tourist place in India therefore high risk of anthropogenic pressure in this ecological niche. Objective: In the present study some pathogenic and nonpathogenic soil bacterial communities earlier isolated and characterized from different microhabitats of Kotumsar cave have been further confirmed by using serological and molecular technique i.e. applying Amplified Ribosomal DNA Restriction Analysis (ARDRA). Methods: Identified bacterial cultures were re-cultured for 16SrDNA analysis. Cluster analysis was used to analyze the restriction pattern generated by the enzyme by the using NTSYS-pc and UPGMA software and as well serotyping is done by Prescott’s method. Result: Total twelve bacteria were selected for serological and molecular characterization. There were two most suitable enzymes EcoRI and AluI which shows typical molecular characteristics between the similar genuses. Conclusion: This piece of work confirms some pathogenic bacteria in Kotumsar cave’s habitat. Though they are not highly pathogenic but repeated visiting in this cave environment may cause infectivity accordingly proper safety precaution must followed after visiting the cave.